Double Allee Effect-Induced Extinction and Bifurcation in a Discrete-Time Predator-Prey Model - Patra, Rajesh Ranjan; Maitra, Sarit; Sarkar, Susmita (Journal of Applied Nonlinear Dynamics, 2026)
The importance of the Allee effect in studying extinction vulnerability is widely recognized by researchers, and neglecting it could adversely impact the management of threatened or exploited populations [1]. In this article, we examine a discrete predator-prey model where the prey population is associated with two component Allee effects. We derive sufficient conditions for the existence and local stability nature of the fixed points of the system. The occurrence of Neimark-Sacker bifurcation is established, and sufficient conditions are obtained along with the normal form. Numerically, we demonstrate that the system exhibits Neimark-Sacker bifurcation for various system parameters. Additionally, the numerical simulations indicate that certain system parameters have threshold values, above or below which the populations are driven to extinction due to the impact of the double Allee effect.